Convective heat and mass transfer in porous media - Kakac, S. (Sadik); NATO Advanced Study Institute on Convective Heat and Mass Transfer in Porous Media (1990 : Izmir, Turkey) (Dordrecht : Kluwer Academic Publishers, 1991)
40